Prevalence of depression, stress, anxiety among information technology professionals during COVID-19 lockdown, 2020 in Kerala - James, Cissy; G., Gopika; Diju, Irina Mariya; T. R., Aswathy; J., Karthika; Jayakumar, Devika; K., Iekshitha; E. R., Bhuvana; P. J., Jayasree; Joseph, Cyril; Tabing, Frincy Alice; M. S., Famiya; et al. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 pandemic has completely changed the work pattern of information technology professionals who had to shift from the work from office to work from home pattern. The comforts of home, that they used to enjoy, was now taken up by an office space at home and this has potentially altered the mental health status of these professionals. Methods: A cross sectional study was conducted among IT professionals within the age group 21-45 years working in Kerala. 218 subjects were included in the study. A self-prepared structured questionnaire was used to collect basic demographic information and depression anxiety and stress scale (DASS 21) scale was used to assess depression anxiety and stress among IT professionals using Google form. Informed consent was obtained in the beginning of the questionnaire. The data was entered in Microsoft Excel and analysed using SPSS software. Results: Out of the total study participants 50.5% (110) were males and 49% (108) were females. 42.7% were married and 57.3% were unmarried and none of them were divorced or living separated. Most of the study participants (62.8%) had monthly income below 50,000. Out of the total study participants, 72 (33%) of them were working in IT field for less than 2 years, 52 were working for last 2-4 years, 51 were working for last 4-8 years and only 43 individuals were working for more than 8 years. 67% of them had their working hours raised during COVID lock down. In our study while 21.6% had a previous history of psychiatric illness for which they have consulted a doctor/psychologist. Out of all the study subjects, 4.1% were mildly depressed, 6.9% were moderately depressed, 5.5% were severely depressed and 1.8% had extremely severe depression. Most of the study subjects (81.7%) were not anxious, 9.2% were mildly anxious, 6.8% were moderately anxious, 2.3% were severely anxious. 76.9% had no stress, 6.1% were mildly stressed, 11.5% were moderately stressed, 4.6% were severely stressed and 0.9% had extremely severe stress. Depression among IT professionals during COVID-19 lockdown was found to be significantly associated with past history of psychiatric illness. Anxiety was found to be significantly associated with past history of psychiatric illness and unmarried relationship status. The stress among IT professionals during lockdown was found to be significantly associated with previous history of psychiatric illness and unmarried relationship status. Conclusions: 18.3% of the IT professionals had some degree of depression and 23.1% was facing stress 18.3% was anxious. Past history of psychiatric illness was associated with increased depression anxiety and stress. Unmarried relationship status was associated with associated with increased anxiety and stress.